2020
DOI: 10.1002/ccd.28803
|View full text |Cite
|
Sign up to set email alerts
|

When antegrade microcatheter does not follow: The “facilitated tip‐in technique”

Abstract: The introduction of retrograde techniques in percutaneous coronary intervention (PCI) of chronic total occlusion (CTO) has significantly improved the success rates. After crossing the CTO lesion in the retrograde approach, wire externalization is a pivotal step to complete the PCI. Many techniques have been described to accomplish externalization in different scenarios of increasing difficulty. We describe the novel "facilitated tip-in technique" which involves the insertion of the back end of an extra-guidewi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Third, insert the retrograde wire into the antegrade microcatheter as far as possible or insert the back end of an extra-guidewire into the antegrade MC, as introduced by Giuseppe Venuti etc. 14 In this study, the overall procedural time and radiation dose showed a trend to decrease in the tip-in group but it had not reached statistical significance yet. Even though the wire externalization process costs more time, externalized wire provides substantial support that may facilitate and expedite other parts of the procedure.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Third, insert the retrograde wire into the antegrade microcatheter as far as possible or insert the back end of an extra-guidewire into the antegrade MC, as introduced by Giuseppe Venuti etc. 14 In this study, the overall procedural time and radiation dose showed a trend to decrease in the tip-in group but it had not reached statistical significance yet. Even though the wire externalization process costs more time, externalized wire provides substantial support that may facilitate and expedite other parts of the procedure.…”
Section: Discussionmentioning
confidence: 53%
“…Third, insert the retrograde wire into the antegrade microcatheter as far as possible or insert the back end of an extra-guidewire into the antegrade MC, as introduced by Giuseppe Venuti etc. 14 …”
Section: Discussionmentioning
confidence: 99%